Pengelolaan Sistem Management Data Kepegawaian di Kantor Camat Lima Puluh - Dhaby Iqbal (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Effective, efficient and structured management of personnel data is an important requirement to support smooth administration and operations in the government environment. This study aims to design and implement a technology-based personnel data management system at the Limapuluh Subdistrict Office, Batu Bara Regency. This system is designed to overcome various problems that arose in previous manual systems, such as data duplication, slow administration processes, and the risk of data loss. The methods used include system requirements analysis through interviews, application-based system design using the Data Flow Diagram (DFD), Sequence Diagram and Class Diagram models, as well as system implementation on available devices. The main features developed include employee data recording, digital attendance, work schedule management, and automatic reporting. The implementation results show that the new system is able to increase the efficiency and effectiveness of personnel data management, speed up the administration process, and increase data security. By training administrative staff, this system also strengthens the human resource management capabilities of the Fifty District Head Office. It is hoped that this research can be a solution and reference for other government agencies that want to digitize personnel data management.